A Comprehensive Review on the Therapeutic Potential of Curcuma longa Linn. in Relation to its Major Active Constituent Curcumin - Fuloria, Shivkanya; Mehta, Jyoti; Chandel, Aditi; Sekar, Mahendran; Rani, Nur Najihah Izzati Mat; Begum, M. Yasmin; Subramaniyan, Vetriselvan; Chidambaram, Kumarappan; Thangavelu, Lakshmi; Nordin, Rusli; Wu, Yuan Seng; Sathasivam, Kathiresan V.; et al. (Frontiers in Pharmacology, 2022)
Curcuma longa (C. longa), popularly recognized as turmeric, is a plant of the Zingiberaceae family having a long historical background of the curative potential against many diseases. In Unani medicine, C. longa has been used for liver obstruction and jaundice conditions and has been applied externally for ulcers and inflammation. Additionally, it is employed in several other ailments such as cough, cold, dental issues, indigestion, skin infection, blood purification, asthma, piles, bronchitis, tumor, wounds, hepatic disorders, antiseptic, etc. Thus, the present review aimed to provide an in-depth discussion of C. longa on taxonomic categorization, traditional uses, botanical description, phytochemical ingredients, pharmacology, toxicity, and safety aspects in relationship with its major compound curcumin to explore the trends and perspectives for future research. C. longa is a source of different form of nutritions like vitamins, minerals, protein, fat, carbohydrate, energy, dietary fibers. Bioactive components reported in C. longa were in the form of curcuminoids (80% curcumin), demethoxycurcumin, and bisdemethoxycurcumin. These components are characterized to exhibit antioxidant, anti-inflammatory, neuroprotective, anticancer, hepatoprotective, cardioprotective, immunomodulatory, antifertility, antimicrobial, antiallergic, antidermatophytic, antidepressant and many more effects. Toxicology studies on rhizome revealed absence of adverse effect even at high oral dose.